2012
DOI: 10.1080/15299732.2012.678471
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic Dissociation and Peritraumatic Emotional Predictors of PTSD in Latino Youth: Results from the Hispanic Family Study

Abstract: This is the first study to examine peritraumatic dissociation and peritraumatic emotions as they predict PTSD symptoms and diagnosis in Latino youth. Our aim was to test the hypothesis that degree of peritraumatic dissociation would predict of number of PTSD symptoms and PTSD clinical diagnosis when the influences of other salient factors were statistically controlled. We also explored the possible contributions of peritraumatic emotional responses to PTSD symptomatology and PTSD diagnosis. We expected that pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…To date, there is no theoretical model that explains the reasons Hispanic youths are at increased risk for detrimental outcomes after exposure to trauma. The scant literature suggests that individual factors such as gender; emotional and cognitive reactions to the trauma (e.g., dissociation, feelings of shame); family factors, such as family conflict and stress; and cultural factors, including low utilization rates of mental health resources, may be associated with poor mental health outcomes following trauma in Hispanic youth (Bridges, de Arellano, Rheingold, Kmett Danielson, & Silcott, 2010; Haller & Chassin, 2012; Vásquez et al, 2012). This article will focus on individual factors, in particular gender of the child, as well as family factors and how they contribute to mental health outcomes in the context of trauma exposure in a clinical sample of Hispanic youth.…”
Section: Psychiatric Symptoms and Disorders In Hispanic Youth Who Hav...mentioning
confidence: 99%
“…To date, there is no theoretical model that explains the reasons Hispanic youths are at increased risk for detrimental outcomes after exposure to trauma. The scant literature suggests that individual factors such as gender; emotional and cognitive reactions to the trauma (e.g., dissociation, feelings of shame); family factors, such as family conflict and stress; and cultural factors, including low utilization rates of mental health resources, may be associated with poor mental health outcomes following trauma in Hispanic youth (Bridges, de Arellano, Rheingold, Kmett Danielson, & Silcott, 2010; Haller & Chassin, 2012; Vásquez et al, 2012). This article will focus on individual factors, in particular gender of the child, as well as family factors and how they contribute to mental health outcomes in the context of trauma exposure in a clinical sample of Hispanic youth.…”
Section: Psychiatric Symptoms and Disorders In Hispanic Youth Who Hav...mentioning
confidence: 99%
“…Peritraumatic emotional reactions have been associated with the development of PTSD symptoms (Bovin & Marx, 2011; Hathaway et al, 2010; Resick & Miller, 2009). Although previous research has emphasized the role of peritraumatic fear, other negative emotions (e.g., anger, sadness, guilt, shame) felt at the time of and in the hours or days immediately following a traumatic event have been linked to increased PTSD symptom severity above and beyond experiences of fear (La Bash & Papa, 2014; Lancaster & Larsen, 2016; Lancaster et al, 2011; Vásquez et al, 2012). Because individuals with difficulty tolerating emotional distress may experience increased PTSD symptoms (Vujanovic et al, 2011, 2013, 2015, 2017), the current study aimed to examine (a) whether overall peritraumatic emotional intensity was related to posttraumatic stress symptoms and (b) if distress tolerance moderated this association.…”
Section: Discussionmentioning
confidence: 99%
“…The group can be an ideal setting for clients to gain understanding of how interpersonal interactions are negatively impacted by shame, while being (paradoxically) maintained by the unhealthy coping mechanisms to avoid these feelings (Counselman, 2008). This is especially important as previous research has indicated that feelings of shame are strongly correlated with long-term instability and development of PTSD following several types of trauma (Deblinger et al, 2016;Vásquez et al, 2012). Moreover, a group therapeutic modality is an ideal setting for the process of "bearing witness," which refers to an individual's moral duty to "testify" to their experience of a traumatic and seminal event and believing it a moral duty to testify to this issue (Figley, 2012).…”
Section: Group Factors That Make It Ideal For Immigrants and Traumamentioning
confidence: 99%